High-sensitivity troponin I for cardiovascular risk stratification in the general asymptomatic population: Perspectives from Asia-Pacific. (1st May 2019) - Lam, Carolyn S.P.; Castillo, Rafael; Ho, Dung Thuong; Kasliwal, Ravi R.; Khurana, Rohit; Naik, Sudhir; Omland, Torbjørn; Parsonage, William Anthony; Phrommintikul, Arintaya; Tobing, Daniel; Yiu, Kelvin Kai Hang
Abstract: Cardiac troponin is a sensitive and specific biomarker for acute myocardial injury and has been used in the diagnosis of acute coronary syndromes, and has emerged as a tool for identifying high risk individuals for primary preventive therapy. Recent evidence has emerged indicating that high-sensitivity cardiac troponin assays, which allow robust detection of very low troponin concentrations, could detect subclinical injury in asymptomatic patients. On 24 March 2018, a group of cardiologists from the Asia Pacific region convened to review the data and discuss the potential utility of high-sensitivity troponin I (hsTnI) in the risk assessment of cardiovascular disease in the general population. The group recognized the immense burden of cardiovascular disease in the Asia-Pacific region, and the limitations of current risk stratification strategies. Data demonstrates that cardiac biomarkers like hsTnI could improve risk stratification, and thresholds for hsTnI in cardiovascular disease risk classification have been developed in Caucasian populations but not validated in Asian populations. There is an urgent need to improve cardiovascular risk assessment in the Asia Pacific general population, validate the Asian threshold of high risk and prove the utility of targeting these high-risk individuals for primary preventive strategies. Highlights: The global burden of cardiovascular disease is burgeoning in Asia Pacific Current cardiovascular disease risk stratification strategies are inadequate Cardiac biomarkers may improve cardiovascular risk assessment in the population There is an urgent need to validate biomarker risk thresholds in Asian populations